Delitos e incidentes de odio hacia personas LGTBI+: prevalencia, consecuencias e impacto - Azabal, Maite (International e-journal of criminal sciences, 2023)
LGTBI+ people still appear to be at greater risk of facing discrimination and being the object of hate crimes and incidents. As can be extracted from official data, hate incidents and hate crimes based on prejudice towards this group are still part of a present reality. This type of victimization has been associated with adverse psychological consequences such as suicidal ideation, post-traumatic stress symptoms and substance abuse, among others. This narrative review aims to approach this reality, analysing the phenomenon in an exploratory way and studying the principal psychosocial outcomes of these events. The evidence indicates that hate crimes and incidents have a unique impact on the mental health of victims that differs significatively from the consequences of those incidents and/or crimes not motivated by prejudice.